2020
DOI: 10.3390/ani10050859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capsicum and Propyl-Propane Thiosulfonate on Rumen Fermentation, Digestion, and Milk Production and Composition in Dairy Cows

Abstract: Essential oils may affect rumen fermentation, nutrient digestion, and milk production and composition. The objective of this study was to test the effects of capsicum oleoresin (CAP) and propyl-propane thiosulfonate (PTSO) on rumen fermentation, total tract digestibility, and milk yield and composition in lactating dairy cattle. Six lactating Holstein cows (averaging (mean ± SD) 130 ± 40 days in milk and 723 ± 55 kg of body weight) fitted with rumen cannulae were used in a duplicated 3 × 3 Latin square design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…With regard to lactose, the greater supply of glucose originating from propionate favors greater milk production, which is closely linked to the synthesis of lactose [ 58 ]. An investigation of the effects of capsaicin on milk composition [ 59 ] reported no effects on milk fat and lactose content, with a trend toward increasing the protein content with respect to the protein content generated with the control treatment. These same researchers noted that there is no clear hypothesis to justify this trend because in their study, rumen degradation of the protein, its digestibility in the total tract, and the proportions of propionate in the rumen were not affected by PE.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to lactose, the greater supply of glucose originating from propionate favors greater milk production, which is closely linked to the synthesis of lactose [ 58 ]. An investigation of the effects of capsaicin on milk composition [ 59 ] reported no effects on milk fat and lactose content, with a trend toward increasing the protein content with respect to the protein content generated with the control treatment. These same researchers noted that there is no clear hypothesis to justify this trend because in their study, rumen degradation of the protein, its digestibility in the total tract, and the proportions of propionate in the rumen were not affected by PE.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, combining phenolics with monoterpenes alcohols has been reported to produce synergistic effects on several microorganisms, in particular, the combination of phenolics (thymol with carvacrol, and both components with eugenol) were synergistically active against Escherichia coli strains [ 178 ]. In ruminants, these combinations were the most effective dietary supplementation options that showed ruminal antimicrobial advantages to modulate the ruminal fermentation pathways [ 179 , 180 ].…”
Section: Challenges and Prospective Of Using Pfas In Animal Nutritionmentioning
confidence: 99%
“…In vivo studies found that oregano and chilli pepper oils increase the performance and quality of animal products (Cardozo et al, 2006;Sanati et al, 2018). In addition, oregano and chilli pepper extracts and their secondary metabolites might act as modifiers of rumen fermentation in beef production systems (Cardozo et al, 2005;Cardozo et al, 2006;Castillejos et al, 2006;Calsamiglia et al, 2007;Foskolos et al, 2020). However, these additives have rarely been shown to modify serum constituents.…”
Section: Introductionmentioning
confidence: 99%